Are rectoceles the cause or the result of obstructed defaecation syndrome? A prospective anorectal physiology study. (29th August 2013) - Hicks, C. W.; Weinstein, M.; Wakamatsu, M.; Pulliam, S.; Savitt, L.; Bordeianou, L.
Abstract: Aim: To determine the relationship between obstructed defaecation syndrome (ODS) and rectoceles. Method: From December 2007 to November 2011, all female patients with ODS were prospectively evaluated with full interview, clinical examination and anorectal physiology testing. The characteristics of patients with and without rectoceles were compared, and logistic regression was utilized to identify factors predictive of patients having a rectocele beyond the introitus. Results: Of 239 patients with ODS, 90 (mean age: 52.3 ± 1.7 years) had a rectocele. Patients with rectoceles (R+) had a similar prevalence of incomplete emptying compared with patients with no rectocele (R−) ( P  ≥ 0.21), but only R+ patients reported splinting with defaecation (36.7% vs 0%; P  < 0.0001). Anorectal manometry measurements, including mean resting pressure, maximum resting pressure and maximum squeeze pressure, were similar between groups ( P  ≥ 0.12). There were also no significant differences in rectal compliance (maximum tolerated volume) or rectal sensitivity (volume of first sensation) ( P  ≥ 0.65). R+ patients had greater difficulty expelling a 60 cm 3 balloon (70.1% R+ patients vs 57.5% R− patients; P  = 0.05), but the prevalence of pelvic floor dyssynergia, as quantified by nonrelaxation on electromyography (EMG) testing, was similar to that of R− patients ( P  = 0.49). Logistic regression suggested that only difficulty with balloon expulsion was associated with higher odds of having a rectocele (OR = 3.00; P  = 0.002), whereas mean resting pressure, EMG nonrelaxation and symptoms of incomplete emptying were not ( P  ≥ 0.12). Conclusion: Rectoceles are not associated with an increased severity of ODS‐type symptoms, anorectal abnormalities or pelvic floor dyssynergia in patients with ODS. This suggests that rectoceles may be the result, rather than the cause, of ODS.